An integrated CP-Based approach for scheduling of processing and transport units in pipeless plants - Zeballos, Luis Javier (2010)
This work addresses the simultaneous production and material handling scheduling problem typically arising in pipeless plants with alternative layouts. An integrated constraint programming (CP) methodology, comprising both a detailed CP model and a suitable search strategy, is developed to address manufacturing environments in which multiple products with different recipes are to be produced. The general pipeless plant topology involves fixed processing stations and a limited number of moveable vessels used to transfer the material between consecutive stations, according to the predefined product recipes. Because of the high combinatorial complexity of the problem, an efficient search methodology is also presented to significantly accelerate the search and reduce the computational effort. The applicability of the proposed integrated CP methodology (model + search strategy) is successfully tested with several challenging examples taken from literature.